Understanding Orangutan Reproduction: Biological Aspects, Climate Change, and Contaminant Exposure - Saka, Raisa Tatum; Sjahfirdi, Luthfiralda; Ariantie, Oriza Savitri (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2025)
Orangutans are arboreal primates and the only great apes native to Asia. Reproduction is crucial for the survival and long-term viability of orangutan populations. This review explores orangutan reproductive biology, focusing on its key features and the potential influences of environmental change. Orangutan (Pongo spp.) reproduction is marked by delayed sexual maturation, long interbirth intervals, and intensive maternal care, reflecting a slow life history strategy. Male bimaturism produces flanged and unflanged forms, each with different mating strategies shaped by social context. Female strategies, such as mate selection and resistance to coercive mating, play a critical role in reproductive outcomes. Climate change, through shifts in rainfall and temperature, is expected to affect food availability, potentially disrupting reproductive timing and offspring survival. The increasing presence of nanoparticles is also considered an emerging threat, though data specific to primates remains limited. Conservation efforts have focused on habitat protection, conflict mitigation, and ex-situ management, including rehabilitation and management of captive individuals in zoos; however, cryopreservation remains largely unexplored.